THE ADDITION OF SIWALAN BORASSUS FLABELLIFER WATER AGAINTS TOTAL HARDNESS LEVEL IN WELL WATER - Christ Kartika Rahayuningsih; Indah Lestari (Jurnal Kesehatan Prima, 2017)
Hardness is the ability of water to form foam when it is mixed with soap. If calcareous water enters the body in excessive amounts in long periods of time can lead to kidney stones disease thus the hardness level in the water must be decreased and one of the methods is the implementation of Siwalan Borassus Flabellifer water, containing lactic acid and alcohol which is capable of dissolving minerals Calcium (Ca2+) in water. The purpose of this study was to determine the effect of the addition of Siwalan Borassus Flabellifer water againts total hardness levels in well water. The analysis is conducted quantitatively and it was experimental study with    complexometric titration method to 5 well water samples taken in the Tuban area by grab sampling technique. From the analyzed samples obtained the average value of total hardness control (without the addition of Siwalan Borassus Flabellifer water) 2626.26 mg/L CaCO3, with the addition of 10 mL Siwalan Borassus Flabellifer water of 2346.54 mg/L CaCO3, the addition of 20 mL of Siwalan Borassus Flabellifer water of 2284.38 mg/L CaCO3, and the addition of 30 mL of Siwalan Borassus Flabellifer water of 2206.68 mg/L CaCO3. The analysis results with statistical test One Way Anova can be concluded that there was no significant effect on the total hardness level of well water with the addition of Siwalan Borassus Flabellifer water.